Effect of Aromatherapy Massage with Chamomile and Lemongrass Oil on Symptoms and Functional Limitations in Patients with Osteoarthritis of the Knee – A Single-Group Experimental Study - Madesh, S.; Deepa, Y.; Mooventhan, A.; Manavalan, N. (Indian Journal of Integrative Medicine, 2025)
Background: Osteoarthritis of the knee (OAK) is one of the most common musculoskeletal conditions, causing joint degeneration and, as a result, difficulty with daily activities. The objective of this study was to assess the impact of aromatherapy massage using lemongrass and chamomile essential oils on the symptoms and functional limitations of patients with OAK. Materials and Methods: In this pre-test and post-test experimental study,50 patients with OAK underwent aromatherapy (lemongrass and chamomile) massage for 20 minutes per day over 10 days. Pre-test and post-test assessments were performed using a visual analogue scale (VAS) for pain and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Statistical analysis was performed using SPSS, version 16. Results: Twenty minutes of aromatherapy (lemongrass and chamomile) massage showed a significant reduction in weight, body mass index, VAS score for pain, and WOMAC scale score in the post-test assessments compared to pre-test assessments in the study group (p